2014
DOI: 10.1038/aps.2014.109
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the nongenomic actions of retinoid X receptor-α by targeting the coregulator-binding sites

Abstract: Retinoid X receptor-α (RXRα), a unique member of the nuclear receptor superfamily, represents an intriguing and unusual target for pharmacologic interventions and therapeutic applications in cancer, metabolic disorders and neurodegenerative diseases. Despite the fact that the RXR-based drug Targretin (bexarotene) is currently used for treating human cutaneous T-cell lymphoma and the fact that RXRα ligands (rexinoids) show beneficial effects in the treatment of cancer and diseases, the therapeutic potential of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 99 publications
1
36
0
1
Order By: Relevance
“…Although RXRα has been recognized as an intriguing drug target for many years, the side effects associated with regulating its transcriptional activity have hampered the development of RXRα‐based drugs (Zhang et al, ). Here, we reported that the sulindac‐derived RXRα modulator K‐80003 significantly mitigated the progression and destabilization of carotid atherosclerotic plaques in ApoE −/− mice without any apparent toxicity to animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RXRα has been recognized as an intriguing drug target for many years, the side effects associated with regulating its transcriptional activity have hampered the development of RXRα‐based drugs (Zhang et al, ). Here, we reported that the sulindac‐derived RXRα modulator K‐80003 significantly mitigated the progression and destabilization of carotid atherosclerotic plaques in ApoE −/− mice without any apparent toxicity to animals.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoid X receptor-α (RXRα) is a unique member of the nuclear receptor superfamily (Zhang et al, 2015), involved in the regulation of several cellular processes including inflammation (Desreumaux et al, 2001;Nunez et al, 2010). Numerous studies have reported the effects of RXRα ligands (rexinoids) on atherogenesis (Claudel et al, 2001;Lalloyer et al, 2006;Staels, 2001;Streb & Miano, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most prominent of these are the steroid hormone receptors — oestrogen receptors (ERα and ERβ), androgen receptor (AR) and progesterone receptor (PR) 43, 44 . In addition to these steroid receptors, accumulating evidence suggests that other NRs (for example, peroxisome proliferator-activated receptor γ (PPARγ) 45 , retinoid X receptor α (RXRα) 46 , truncated thyroid receptor α (TRα) isoforms 44, 47 and retinoic acid receptors (RARα and RARγ 48 )) might also signal via a similar mechanism. Non-genomic signalling does have the potential to affect the genome and alter transcription, as kinases activated in non-genomic signaling pathways can phosphorylate and regulate the activity of epigenomic programmers, transcription factors and/or their associated coregulators, even in the absence of a liganded NR interacting with target genes.…”
Section: Liver Fat Metabolism and Edcsmentioning
confidence: 99%
“…In addition to their functions in transcription control, nuclear receptors are also involved in nongenomic actions of cell response to hormones and they are also targeted by regulation of signaling from cell surface receptors. Zhang and coworkers provide a detail review of regulation of nongenomic actions of retinoid X receptor-α by targeting the coregulator-binding sites [10] . Li and coworkers review the signaling cascade from cell surface receptors to nuclear receptors in the pathways of bile acid metabolism [11] .…”
Section: Editorialmentioning
confidence: 99%